Antibacterial Compounds of Actinomycetes Isolated From Altitude Soils - Aryal, Sagar; Adhikari, Rameshwar; Regmi, Balmukunda; Joshi, Dev Raj (Journal of Nepal Health Research Council, 2025)
Background: Bacterial infection is a global threat due to antibiotic resistance. This demands the urgent need for novel antibiotics, and soil actinomycetes could be the potential candidate. The key objective of our study was to detect antibacterial compounds from selected actinomycetes species isolated from high-altitude soil samples. Methods: Three strains Streptomyces sp. 12923, Streptomyces sp. 13102, and Nocardia sp. 13105 were subjected to fermentation using International Streptomyces Project (ISP) 2 medium. Crude extracts of each isolate were recovered by Rotary evaporator. Crude extracts were fractionated in HPLC and fractions were collected in a 96-well plate to evaluate the antibacterial activity of each of the 19 fractions against a test organism E. coli BW25113. Crude extracts of three strains were analyzed using UPLC-MS/MS for antibacterial compounds. The LC-MS/MS data were processed using Metabo Scape software and features were annotated using different libraries in the software. Results: For Streptomyces sp. 12923, fractions of the crude extract with the lowest OD600 0.472, 0.484 showed higher antibacterial activity against E. coli BW25113T, while the inhibitory action against same test organism was shown better by fractions OD600 0.250, 0.329, and OD600 0.273, 0.326 for Streptomyces sp. 13102 and Nocardia sp. 13105, respectively. The antibacterial compounds detected included Mayamycin and Mayamycin B from Streptomyces sp. 12923, Nocardamine and Streptazone D from Streptomyces sp. 13102, and Nocardimicin B, 4-O-methylmelleolide, Spathullin B and Nannozinone B from Nocardia sp. 13105. Conclusions: The identification of these compounds from high-altitude actinomycetes further strengthens the claim that actinomycetes are rich sources of bioactive compounds. Keywords: Actinomycetes; antibacterial; metabolites; Nocardia; Streptomyces.